Analyze The Marketing Mix Strategy In Enhancing The Competitiveness Of Bank Permata Community Channel Division - Theresia Magdalena Massie (Green Publisher Indonesia, 2024)
This study aims to analyze the marketing mix strategy in enhancing the competitiveness of Bank Permata's Community Channel Division. The marketing mix strategy, consisting of product, price, place, promotion, people, process, and physical evidence (7P), is applied to understand how each element contributes to the bank's competitive advantage. The research method used is qualitative with a case study approach, involving in-depth interviews with managers and staff of the Community Channel Division, as well as analysis of internal bank documents and reports. The results of the study indicate that the effective implementation of the marketing mix strategy can enhance customer satisfaction, loyalty, and brand image, ultimately improving Bank Permata's competitiveness. These findings provide practical recommendations for Bank Permata's management to continuously optimize their marketing strategies to achieve sustainable competitive advantage.